2008 31st International Spring Seminar on Electronics Technology 2008
DOI: 10.1109/isse.2008.5276669
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure analysis and measurement of nonlinearity of vapour phase reflowed solder joints

Abstract: Abstract. The goal of the study is to compare quality of lead-free vapour phase reflowed solder joints soldered on different printed circuit board (PCB) surface finishes. The solder joints quality comparison is based on evaluation of microstructure development of the solder, solder/PCB pad interface and on the measurement of the solder joints nonlinearity of the current-voltage (C-V)characteristics. The microstructure is evaluated before and after accelerated ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Applying Eq. (6), (7) and (8) along with the boundary conditions to all nodes using continuous indexing result in a system of simultaneous (implicit) equations in every phase. It can be expressed with matrices in the general from of A•T n+1 =B•T n +C, where double underline refers to square matrices and single underline represents column vectors.…”
Section: Adi Scheme For Non-homogeneous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying Eq. (6), (7) and (8) along with the boundary conditions to all nodes using continuous indexing result in a system of simultaneous (implicit) equations in every phase. It can be expressed with matrices in the general from of A•T n+1 =B•T n +C, where double underline refers to square matrices and single underline represents column vectors.…”
Section: Adi Scheme For Non-homogeneous Materialsmentioning
confidence: 99%
“…Recently VPS was compared directly with more conventional convection type reflow by Dziurdzia [6], while the others focused more solely on VPS. It was found by Pietrikova [7] and Liu [8] that the microstructure of the joints formed in VPS ovens are dependent of the given setting and mode of the applied ovens.…”
Section: Introductionmentioning
confidence: 99%
“…Others showed that the microstructure of the joints formed in VPS ovens are dependent of the given setting of the soldering profile in vapours. [10][11]. Setting of this profile [12] or optimizations with statistical methods [13] were also investigated.…”
Section: Fig 1 Scheme Diagram Of Vps Ovenmentioning
confidence: 99%
“…Vacuum VPS was also investigated by Lungen et al (2015), where the research team pointed to the quality improving importance of a proper temperature profile setting and the void reducing capability of the vacuum. Many research teams (Hurtony et al, 2012;Pietrikova et al, 2008;and Liu et al, 2015) inspected the microstructural characteristics of the VPS soldered joints, which are highly affected by the temperature settings of the process. Not only can the overall structure of the joint be influenced by different heating mechanisms but also the intermetallic layer is affected by different parameters of the heating.…”
Section: Introductionmentioning
confidence: 99%